1994
DOI: 10.1002/hrm.3930330403
|View full text |Cite
|
Sign up to set email alerts
|

Announced layoffs: Their effect on corporate financial performance

Abstract: L Conventional wisdom holds that when a firm gets into trouble due to lagging sales and rising costs, cutting the size of the organization to reduce fat and waste is a normal and effective response. In this study, euidence was found to suggest that just the opposite might be true. The financial performance of Fortune 100 companies was tracked over a five-year period-two years prior to the announced layof, the year of the layof announcement, and two years following it. Contrary to expectations, the results indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
136
1
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(146 citation statements)
references
References 7 publications
2
136
1
3
Order By: Relevance
“…The digital economic data will be analyzed using the published of Indonesia government report including the strategic development of telecommunication infrastructure and also stated by the Economist Intelligence Unit (EIU) [22], which include: the ICT infrastructure (X 1 ), the business environment (X 2 ), the social and cultural environment (X 3 ) and consumer and business adoption (X 4 ). The downsizing strategy (Y 1 ) was characterized by the reducing the number of current employees [14] and for the banking performance will be measured by the rate of customer satisfaction (Y 2 ), the bank image (Y 3 ), and the bank's financial performances (Y 4 ) [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The digital economic data will be analyzed using the published of Indonesia government report including the strategic development of telecommunication infrastructure and also stated by the Economist Intelligence Unit (EIU) [22], which include: the ICT infrastructure (X 1 ), the business environment (X 2 ), the social and cultural environment (X 3 ) and consumer and business adoption (X 4 ). The downsizing strategy (Y 1 ) was characterized by the reducing the number of current employees [14] and for the banking performance will be measured by the rate of customer satisfaction (Y 2 ), the bank image (Y 3 ), and the bank's financial performances (Y 4 ) [17].…”
Section: Methodsmentioning
confidence: 99%
“…Downsizing is the systematic reduction of a workforce through an internationally instituted set of activities by which organizations aim to improve efficiency and performance [13], [5]. De Meuse [14] defined downsizing as -a large permanent, reactive layoffs, a streamlining of functions, a redesign of systems, a redefinition of policies aimed at cutting costs and a proactive strategy.‖ Bank and Tustin [15] posited that downsizing is one tactic within a corporate strategy for shifting the organizational structure from what it is now to what it has to be in order to sustain competitive edge and satisfy customer's needs. The reason advanced for downsizing is also to improve service delivery and promote good governance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[24] found that companies laying off 10% or more of the work force significantly underperformed firms laying off less on profit margin, ROA, ROE, and market-to-book ratio. [8] found, the announced layoffs do not enhance financial performance. Based on [16] work, the improvement of financial performance (ROA) by retrenching was found to be greater among companies that had not experienced any loss than among those that had experienced loss.…”
Section: Literature Reviewmentioning
confidence: 96%
“…During the current global financial crisis, firms and corporations are searching for strategies to enable them to survive and sustain their profitability. These firms retrenched or retrench so that they can (a) reduce operating costs, (b) eliminates unnecessary level of management, (c) streamlines operations, (d) enables an organisation to prune deadwood, (e) enhances overall effectiveness, and (f) ultimately, makes a firm more competitive in today's market place [3]- [8] found that the evidence suggests retrenching is more likely to be effective when it is part of an organization's overall long-term strategic planning process.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation